2015
DOI: 10.3390/antiox4020359
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between Leave of Apocynum venetum and Its Adulterant, A. pictum Based on Antioxidant Assay and Chemical Profiles Combined with Multivariate Statistical Analysis

Abstract: An integrated approach including chemical and biological assessments was developed to investigate the differences between Apocynum venetum L. (AV) and its adulterant, Apocynum pictum Schrenk (AP). Ten flavonoids were tentatively identified by ultra-visible and mass spectra data. The chemical component, hyperoside, was identified as a critical parameter for discrimination of two species from the results of principal component analysis (PCA) and quantitative analysis. The anti-oxidative power of the herbal extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…19 . Previous studies using DPPH assay and our results tested by DPPH and FRAP indicated that A. venetum has high antioxidant capacity 28,29 , which were similar with that of common black tea. Li application did not decrease the antioxidant capacity in A. venetum .…”
Section: Discussionsupporting
confidence: 77%
“…19 . Previous studies using DPPH assay and our results tested by DPPH and FRAP indicated that A. venetum has high antioxidant capacity 28,29 , which were similar with that of common black tea. Li application did not decrease the antioxidant capacity in A. venetum .…”
Section: Discussionsupporting
confidence: 77%
“…The results show the amount of flavonoids compounds selected in the two species to have varied tremendously in accordance with the LC/MC profile ( Table 5). The highest level of isoquercitrin (5.254 mg/g of DW, dry weight) was obtained in A. venetum, which was significantly higher than that obtained in A. hendersonii (1.718 mg/g of DW), suggesting that, in addition to hyperoside [7], isoquercitrin could also be a good chemical marker to differentiate A. venetum and A. hendersonii. The amount of total anthocyanins was determined using the previously described pH differential method.…”
Section: Analysis Of Flavonoids Biosynthesis-related Transcript Levelmentioning
confidence: 74%
“…A. venetum, in addition to serving as source of bast fiber, is very well known for possessing broad medicinal uses as anti-platelets [4], anti-depressive [5], anti-hypertensive [6], anti-oxidant [7], anti-aging [8], anxiolytic activity [1], stimulant as tea [9] etc. Meanwhile, A. hindersonii is morphologically similar to A. venetum but with a major visible distinction being in the color of stem and leaf, and the shape of their flower, owing likely to their local names "White Hemp" and "Red Hemp", respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that A. venetum has a higher flavonoid content than its related species Apocynum. hendersonii , and some flavonoid components such as hyperoside have been identified as suitable chemical markers for the discrimination of the two species [ 34 ]. In a recent metabolome and transcriptome analyses of Apocynum, Gao et al [ 21 ] found that the flavonoid biosynthetic pathway is responsible for a considerable proportion of the diversity between A. venetum and A. hendersonii , and identified anthocyanin as the key component that determines the phenotypic diversity of the stem and leaf color of A. venetum and A. hendersonii .…”
Section: Discussionmentioning
confidence: 99%